The moderating effects of slack on the relationship between ambidextrous strategy and performance: evidence from high-tech firms in China - Luo, Biao; Luo, Changyue; Ge, Jiajia; Zhang, Dongli (Journal of Business Economics and Management, 2016)
The purpose of this study is to examine the impacts of ambidexterity of exploration/exploitation on long-term performance and the moderating effects of slack resources. The methodology adopted is panel data analysis of a sample dataset of 125 high technology firms in China. The finding of this study shows that a moderating role of organizational slack between ambidexterity and long-term performance is strongly supported. The research and practical implications of this paper are: (1) Exploration and exploitation can be mutually enhancing instead of being fundamentally contradictory; (2) Slack resources moderate the relationship between ambidexterity and performance. The originality and value of the paper is that it is one of the earliest studies that empirically examine the moderating effects of slack resources on ambidexterity-performance relationship.